2000
DOI: 10.2116/analsci.16.1277
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Monoaza-, Diaza-, or Polyazacrown Ethers and Alkali Metal Ions in Acetonitrile by Polarography

Abstract: Crown-type compounds are of general relevance as synthetic model substances for studying physiological ion-transport processed in biological membranes, for investigating receptor and enzyme interactions as well as for the salt balance and for metabolic processes of living organisms. 1 The complexation between alkali metal ions and macrocyclic polyethers, polyamines or polyetheramines has been extensively studied by means of various methods in many solvent systems. 2,3 The fitness of the cavity size of a macroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Their stronger binding was demonstrated both in absorption and fluorescence experiments, in which fluorescence increased by up to 100 Â and F F reached values of approximately 0.20. The stronger binding of alkaline earth metal cations is in accordance with published data in which different methods (i.e., absorption spectroscopy of chromoionophores [27], polarography [28], or laser infrared multiple photon dissociation spectroscopy [23]) were applied.…”
Section: Discussionsupporting
confidence: 87%
“…Their stronger binding was demonstrated both in absorption and fluorescence experiments, in which fluorescence increased by up to 100 Â and F F reached values of approximately 0.20. The stronger binding of alkaline earth metal cations is in accordance with published data in which different methods (i.e., absorption spectroscopy of chromoionophores [27], polarography [28], or laser infrared multiple photon dissociation spectroscopy [23]) were applied.…”
Section: Discussionsupporting
confidence: 87%
“…Starting from 1-aza-15-crown-5 ether (a15c5), reductive amination provides m -(aza-15-crown-5)­methylphenol ( 1 , Chart S1 in the Supporting Information). , The pincer-crown ether ligand precursor 1 binds Li + and Na + cations tightly in a 1:1 fashion in CD 3 CN at 25 ± 1 °C, as evidenced by the linear response of 1 H NMR spectroscopic titrations up until 1 equiv of the cation relative to the macrocycle. A competitive binding technique (see Section S2 in the Supporting Information) provided association constants ( K a ) for 1 with both LiOTf ( K a (Li + ) = 130000 ± 4000 M –1 ) and NaBAr F 4 ( K a (Na + ) = 79000 ± 4000 M –1 , Ar F = 3,5-bis­(trifluoromethyl)­phenyl) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…[28,29] This is surprising since different cryptand/cryptate or crown ether-solvent combinations have been investigated, [30][31][32][33][34] especially with respect to their transport properties [35] or ion conductivity and potential applications in batteries and capacitors, [36] while parallel alkali and alkaline-earth ion complexes with phenanthroline and bipyridine moieties have also been studied. [37] In a recent report we demonstrated that ion selectivity can be studied by quantum chemical methods for [2.2.2] and smaller homologues.…”
Section: +mentioning
confidence: 99%